Uso invernal de la remolacha forrajera en pastoreo con ovejas. Comunicación = Winter use of forage beet in grazzing with ewes. Comunication - Ceballos, Demian; Villa, Martin Diego; Lexow, Guillermo; Bobadilla, Segundo Evaristo; Dellacanonica, Cristina; Favere, Verónica Mariela (Asociación Argentina de Producción Animal, 2023)
Publicado en: Revista Argentina de Producción Animal. v. 42, Sup. 1, p. 324